Peningkatan Kualitas Guru SMK Kabupaten Nganjuk Melalui Pelatihan Penulisan Karya Ilmiah - Witjaksono, Andre Dwijanto; Wijayati, Dewie Tri; Iriani, Sri Setyo; Hartono, Ulil; Rozaq, Khoirur (Universitas Negeri Surabaya, 2022)
Abstract Teachers' writing skills are needed to support the demands of professionalism, especially related to career development and scientific needs. The lack of scientific work produced by teachers such as articles, books and modules is a challenge that is a challenge in the world of education. Because many opportunities support the development of writing skills: the service team organizes scientific article writing training activities for teachers of creative products and entrepreneurship subjects to improve motivation and scientific writing skills. (1) The entrepreneurship teacher has a field practicum program that can be used as writing material. (2) In developing innovative products, teachers and students make a lot of observations that can be downstream into scientific works. (3) The academic climate where teachers constantly interact with the world of science. The training implementation uses a hybrid offline and online learning system. The training materials were delivered using lecture, discussion, case studies and direct simulation methods. The results of the comparison of the participants' pretest and posttest showed that there was an increase in participants' understanding and skills in writing scientific papers. The results of the evaluation of the training implementation activities also showed that the participants were delighted with the services provided by the community service team. The results of this scientific work will undoubtedly support teachers' professional careers, namely promotion and class. Keywords; Article writing, scientific journals, management, entrepreneurship